Handbook of dairy foods analysis - Nollet, Leo M. L., 1948-; Toldrá, Fidel (CRC Press, 2009)
"Dairy foods account for a large portion of the Western diet, but due to the potential diversity of their sources, this food group often poses a challenge for food scientists and their research efforts. Bringing together the foremost minds in dairy research, Handbook of Dairy Foods Analysis compiles the top dairy analysis techniques and methodologies from around the world into one, well-organized volume. Exceptionally comprehensive both in its detailing of methods and the range of products covered, this handbook includes tools for analyzing chemical and biochemical compounds and also bioactive peptides, prebiotics, and probiotics. It describes noninvasive chemical and physical sensors and starter cultures used in quality control. The book discusses current methods for the detection of microorganisms, allergens, and other adulterations, including those of environmental origin or introduced during processing. Other methodologies used to evaluate color, texture, and flavor are also discussed."--Publisher's description
Keywords: Dairy products -- Analysis -- Handbooks, manuals, etc.; elektronické knihy; electronic books